CURRENT VIEWS ON THE PATHOGENESIS AND EARLY DIAGNOSIS OF ACTINIC KERATOSIS - A.A. SYDIKOV; G.B. PYAGAY; O.G. PYAGAY (Avicenna Tajik State Medical University, 2023)
The article provides an overview of the epidemiology and pathogenesis of actinic keratosis (AK) and its clinical differentiation from cutaneous squamous cell carcinoma (SCC). The authors present varying perspectives on the prognosis of the disease's development and its pathogenetic link to SCC, highlighting the significance of early diagnosis of the malignant transformation. Researchers suggest several markers, such as p16, p53, and p63, to identify the malignant transition in its early stages. The authors support their hypothesis by offering that mutations in genes that express these proteins directly impact the progression of the disease. Another group of authors, recognizing the significant role of inflammation in the pathogenesis of AK, suggest determining the level of various cytokines, emphasizing the essential role of UV radiation in triggering the entire pathogenetic cascade of AK development. Meanwhile, most authors acknowledge that various proteins act as early immunohistochemical (IHC) markers of an unfavorable disease prognosis. They describe the pathogenetic mechanisms of the effect of markers such as p16, p53, p63, and Bcl-2. Research is underway to identify new markers, such as claudin and T-cadherin. In August 2023, a search was conducted on the PubMed Clinical Queries database using keywords such as "actinic keratosis", "pathogenesis of actinic keratosis", and "progression of actinic keratosis to squamous cell carcinoma" to look for early markers of malignancy. The search strategy included clinical trials, observational studies, case reports, and literature reviews published in the last decade. However, sources without peer review, such as educational and methodological guidelines, recommendations, and conference proceedings, were excluded. The information obtained through this search was used to compile this article, and promising directions for the search for early malignancy markers were identified.